Unlocking building biographies during the Late Bronze Age in Central Macedonia: the case of the Thessaloniki Toumba mound settlement - Efkleidou, Kalliopi; Karantoni, Maria; Triantaphyllou, Sevasti; Andreou, Stelios (Journal of Greek Archaeology, 2022)
The scope of the present paper is to scrutinise the evidence regarding settlement continuity, especially where continuous replication of the same buildings is involved, and to investigate how it was practiced in Late Bronze Age mound settlements in terms of building methods. Furthermore, we aim to investigate how building continuity or change related to people’s lives and the spatial organisation of their mundane activities and social practices which concerned their biological and social reproduction.